2016
DOI: 10.1186/s12933-016-0335-3
|View full text |Cite
|
Sign up to set email alerts
|

Is visceral adiposity a modifier for the impact of blood pressure on arterial stiffness and albuminuria in patients with type 2 diabetes?

Abstract: BackgroundWe aimed to investigate whether visceral adiposity could modify the impact of blood pressure on arterial stiffness and albuminuria in patients with type 2 diabetes.MethodsThis cross-sectional study examines the interaction of visceral adiposity with increased blood pressure on arterial stiffness and albuminuria. 638 patients with type 2 diabetes (mean age 64 ± 12 years; 40 % female) were enrolled. Visceral fat area (VFA, cm2) was assessed by a dual-impedance analyzer, whereby patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The exact etiology of cardiovascular diseases and decreased muscle quality in T2DM with visceral fat accumulation is unknown. Dysregulation of adipocytokines/adipokines, such as hypoadiponectinemia, has been reported previously [ 40 ], and the high levels of inflammatory cytokines in the accumulated visceral fat could result in systemic low-grade inflammation, insulin resistance, microalbuminuria [ 41 , 42 ], arterial stiffness [ 43 ], and atherosclerotic cardiovascular diseases [ 40 , 44 ]. In fact, hypercytokinemia, including high serum levels of tumor necrosis factor-α and interleukin 6 (IL-6), has been reported to be associated with both muscle mass and muscle strength in the elderly [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 95%
“…The exact etiology of cardiovascular diseases and decreased muscle quality in T2DM with visceral fat accumulation is unknown. Dysregulation of adipocytokines/adipokines, such as hypoadiponectinemia, has been reported previously [ 40 ], and the high levels of inflammatory cytokines in the accumulated visceral fat could result in systemic low-grade inflammation, insulin resistance, microalbuminuria [ 41 , 42 ], arterial stiffness [ 43 ], and atherosclerotic cardiovascular diseases [ 40 , 44 ]. In fact, hypercytokinemia, including high serum levels of tumor necrosis factor-α and interleukin 6 (IL-6), has been reported to be associated with both muscle mass and muscle strength in the elderly [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 95%
“…As a cardiometabolic disease, diabetes is associated with 2–4 times higher risk of CVD and it double the risk of cardiovascular mortality [ 38 41 ]. Previous studies have documented that ectopic fat accumulation, mainly visceral adipose tissue, acting through the potential inflammatory response and oxidative phosphorylation pathways [ 42 ], is a risk factor of metabolic disorders, atherosclerosis, and CVD [ 3 , 43 45 ]. The failure of visceral adipose tissue to store triglyceride could result in an increase of epicardial adipose tissue thickness [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aortic PWV has also been established as an independent predictor of future cardiovascular events and mortality [27, 28]. Recent studies have shown a close association between blood pressure and arterial stiffness as evaluated by brachial-ankle PWV [29] in patients with type 2 diabetes, and a predictive value of brachial-ankle PWV on the progression of coronary artery calcification [30] The results from the present study are in agreement with those of the previous study [15] and indicate a possible role of LBP in the progression of atherosclerosis. Furthermore, this study is the first to report the impact of LBP on arterial stiffness in patients with type 2 diabetes, who have advanced arterial stiffening [22, 27, 3133] and elevated cardiovascular mortality [34].…”
Section: Discussionmentioning
confidence: 99%